l(1)hopscotch, A larval-pupal zygotic lethal with a specific maternal effect on segmentation in Drosophila. - Perrimon, N.; Mahowald, A.P. (Developmental Biology, 1986)
The maternal and zygotic effect phenotypes of mutations at the l(1)hopscotch (l(1)hop) locus are described. l(1)hop is located in 10B6-8 on the salivary gland chromosome map and 17 alleles have been characterized. A complex complementation pattern is observed among the 17 alleles. The lethal phase of null alleles of l(1)hop occurs at the larval-pupal interface associated with a small disc phenotype. Embryos produced from homozygous l(1)hop germline clones show segment specific defects. The extent of these defects depends upon both the strength of the allele and the paternal contribution. In the most extreme case embryos exhibit defects associated with five segments T2, T3, A4, A5, and A8. In the less extreme phenotype defects are only associated with A5. Thus, activity of l(1)hop+ is required both for the maintenance and continued cell division of diploid imaginal precursors and for the establishment of the full array of segments.